(untitled) (Journal of Informatics and Mathematical Sciences, 2016)
Fast compressive tracking algorithm performs more effective and robust than some other state-of-art tracking algorithm, it crop samples from the current frame, all these samples have the same weighted in learning procedure, in order to integrates the sample importance into the learning procedure, motived by the weighted multiple instance learning algorithm, we present a novel enhanced fast compressive tracking, which integrates the samples importance into learning procedure. Experimental results on various benchmark video sequences demonstrate the superior performance of our algorithm.